Pengaruh Job Insecurity Terhadap Turnover Intention Karyawan Bagian Sales dimediasi Kepuasan Kerja - Monica Sara Risambessy; Conchita Valentina Latupapua; Harvey Hiariey (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2024)
Turnover intention is the desire of employees to quit their jobs in order to get another job. This study aims to analyze job insecurity against turnover intention mediated job satisfaction. The sample in this study was 51 sales employees at Kredit Plus (PT Finansia Multi Finance) Ambon Branch and used a simple random sampling method. Data collection was carried out by distributing questionnaires using Likert scale. The analysis tool used in this study is Smart PLS 3.0 software. The results obtained from this study are: (1) job insecurity has a positive and significant effect on turnover intention, (2) job insecurity has a negatif and significant effect on job satisfaction (3) job satisfaction has a negatif and significant effect on turnover intention (4) job satisfaction does not mediate the effect of job insecurity on turnover intention.